BUILDING AND DEVELOPING VIETNAMESE CULTURE: FROM POLICY TO PRACTICE - Thi Thanh, Trinh (2021)
Culture plays an important role in the spiritual life of Vietnamese people. In the process of national construction and development, as a ruling party, the Communist Party of Vietnam has been aware of the position, role, and importance of culture. In many of its policies, the Communist Party of Vietnam has issued many guidelines and guidelines for building and developing Vietnam's culture. In particular, in recent years, many policies on culture have been promulgated and gradually entered into practice, bringing many practical results to the construction of people's lives and participation in building and developing the country. This study clearly shows the cultural policy of Vietnam in history, the process of penetrating into real life and proposes solutions to continue building and developing an advanced Vietnamese culture imbued with ​identity nation.